The feasibility of wildlife immersion experiences for Veterans with PTSD - Perry, Donna J.; Crawford, Sybil L.; Mackin, Jill M.; Averka, Jesse J.; Smelson, David A. (Frontiers in Veterinary Science, 2024)
Introduction: Animal-assisted interventions (AAI) offer potential physical and psychological health benefits that may assist Veterans with post-traumatic stress disorder. However, more feasibility studies are needed regarding intervention details, adverse events, reasons for study withdrawal, and animal welfare. Methods: This mixed methods feasibility trial involved a modified crossover study in which Veterans with PTSD/ PTSD symptoms were provided a series of 8 nature and wildlife immersion experiences to evaluate feasibility and preliminary efficacy. The sample included 19 Veterans with PTSD/ PTSD symptoms who were followed for a mean of 15.1 weeks. The intervention was comprised of a baseline forest walk, assisting with wildlife rehabilitation, observation in a wildlife sanctuary, and bird watching. Post study bird feeders were provided for sustainability. The theory of transcendent pluralism, which is grounded in mutual human-ecological dignity, guided the study.Results: This AAI nature/ wildlife immersion intervention was feasible, acceptable, and safe to administer to Veterans with PTSD/ PTSD symptoms with appropriate support. Logistical and relational facilitators were identified that supported the wildlife immersion activities. Participants reported greatly enjoying the activities. Attention to animal welfare and care was an important ethical foundation that also contributed to feasibility. Discussion: AAI immersion experiences with wildlife are feasible and can safely be administered to Veterans with PTSD/ PTSD symptoms. Logistical and relational facilitators are important to support nature and wildlife immersion activities.